Penerapan Metode First Come First Served (FCFS) Pada Sistem Informasi Layanan Perawatan dan Perbaikan Aset Kampus - Riyadi Purwanto; Linda Perdana Wanti; Ratih Hafsarah Maharrani; Rostika Listyaningrum (Infotekmesin, 2022)
Assets are resources owned by an entity. Cilacap State Polytechnic is a higher education institution that has many assets. Current asset maintenance and repair services are still carried out conventionally. Each work unit must fill out a maintenance and repair proposal form and then submit it to the Maintenance, Repair, and Maintenance Unit (UP3). The proposal will be recorded and scheduled to be followed up by the Technician. The problem that occurs is that the proposal form is often scattered and even lost so the response time is often slow. In addition, maintenance and repair schedules are often not ordered according to the time of the request. This has an impact on the abandonment of work in certain work units. The purpose of this research is to create an information system for the repair and maintenance of campus assets. In order for maintenance and repair services to be carried out according to the time of the request, the FCFS method is applied. Thus, the service process for maintaining and repairing campus assets becomes more organized, schedules (queues) are sequenced, and the response time for incident handling is faster.